Faith, Identity Processes and Science-Based Project Learning Methods for Madrasah Teachers - Syahraini Tambak; M. Yusuf Ahmad; Desi Sukenti; Ermalinda Siregar (AL-ISHLAH: Jurnal Pendidikan, 2022)
The development of students' scientific thinking in the field of akidah akhlak (moral theology) is very urgent, and for that process, a science-based project learning method is needed. This study uses a phenomenological approach to explore the involvement of faith and identity processes of madrasah aliyah teachers in developing science-based project learning methods, involving twenty moral theology teachers, conducted in-depth interviews to reveal the narrative of teachers' practice in using science-based project learning methods. Thematic analysis of two-group interviews with 20 teachers showed that teachers' personal beliefs provided a religiously-motivated narrative framework that facilitated the interpretation of one's experiences. The involvement of personal faith and religiosity, identity processes when teaching, plays a role in the development of science-based project learning methods on moral theology. The application of Islamic principles and faith is the main bond in the development of science-based project learning methods and attribution of identity from God-given personality to learning in moral theology. Identity processes, faith, and scientific thinking of students develop when following the learning of moral theology. In conclusion, this exploratory study shows that faith and identity processes in personal can improve science-based project learning methods. In the future, large-scale research could provide further evidence to reconsider the role of religious education in teacher training as an important factor in developing science-based project learning methods for teachers of moral theology.